The Effect of Fair Value versus Historical Cost Reporting Model on Analyst Forecast Accuracy - Liang, Lihong; Riedl, Edward J. (The Accounting Review, 2014)
ABSTRACT This paper examines how the reporting model for a firm's operating assets affects analyst forecast accuracy. We contrast U.K. and U.S. investment property firms having real estate as their primary operating asset, exploiting that U.K. (U.S.) firms report these assets at fair value (historical cost). We assess the accuracy of a balance-sheet-based forecast (net asset value, or NAV) and an income-statement-based forecast (earnings per share, or EPS). We predict and find higher NAV forecast accuracy for U.K. relative to U.S. firms, consistent with the fair value reporting model revealing private information that is incorporated into analysts' balance sheet forecasts. We find this difference is attenuated when the fair value and historical cost models are more likely to converge: during recessionary periods. Finally, we predict and find lower EPS forecast accuracy for U.K. firms when reporting under the full fair value model of IFRS, in which unrealized fair value gains and losses are included in net income. This is consistent with the full fair value model increasing the difficulty of forecasting net income through the inclusion of non-serially correlated elements such as these gains/losses. Information content analyses provide further support for these inferences. Overall, the results indicate that the fair value reporting model enhances analysts' ability to forecast the balance sheet, but the full fair value model reduces their ability to forecast net income.